2014
DOI: 10.1080/19761597.2014.912577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of activity in open-source communities using social network analysis techniques

Abstract: The success of an open-source software project is closely linked to the successful organization and development of the underlying virtual community. In particular, participation is the most important mechanism by which the development of the project is supported. The main objective of this paper is to analyse the online participation in virtual communities using social network analysis techniques in order to obtain the main patterns of behaviour of users within communities. Several open-source communities rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Projects typically begin in the first stage, with new developers being brought in onto the lower tier of development over time. In an extension of this work Martínez-Torres [17] found that the core team of developers are responsible for bringing in these new developers, showing former connections are valuable. Similarly, Allaho and Lee [18] using very large datasets from Ohloh and GitHub, found that as new developers join, developers with higher levels of expertise will partner with newer developers, adding them into the project.…”
Section: Hierarchymentioning
confidence: 80%
“…Projects typically begin in the first stage, with new developers being brought in onto the lower tier of development over time. In an extension of this work Martínez-Torres [17] found that the core team of developers are responsible for bringing in these new developers, showing former connections are valuable. Similarly, Allaho and Lee [18] using very large datasets from Ohloh and GitHub, found that as new developers join, developers with higher levels of expertise will partner with newer developers, adding them into the project.…”
Section: Hierarchymentioning
confidence: 80%
“…Other factors enhancing idea generation were the variety of roles users assume, the heterogeneity of the community, and the moderating role of company employees triggering discussions and engaging with the community [ 47 , 114 , 124 ]. Authors also investigated specific structural characteristics of open innovation communities and communication patterns [ 110 , 125 132 ]. By examining the effect of specific network structures, Singh, for example, showed that small-world properties of an online community led to successful projects in terms of code development as well as user acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…Network analysis, a method first introduced in sociology, enables us to analyze the structure of a network that consists of connections among people and then use such analysis to interpret various social phenomena (Iacobucci and Hopkins, 1992;Martínez-Torres, 2014). Henderson et al (1998), working from the premise that consumers' brand associations also form network structures, applied various concepts and methods used in network analysis to elicit and analyze brand association networks from consumers.…”
Section: Brand Positioning Through Web Search Traffic Informationmentioning
confidence: 99%